Effectiveness of gerontologically informed nursing assessment and referral interventions for older persons attending the emergency department: systematic review. - Fealy, G; McCarron, M; O'Neill, D; McCallion, P; Clarke, M; Small, V; O'Driscoll, A; Cullen, A (2009)
AIM: This paper is a report of a literature review conducted to analyse data from published studies reporting nursing interventions targeted at older attendees of emergency departments (EDs), and to provide a critical appraisal of the evidence concerning their effectiveness. BACKGROUND: Attendance at hospital EDs by older persons presents opportunities for targeted interventions to address actual and potential problems associated with or in addition to the presenting problem. The evidence concerning the effectiveness of such interventions is mixed. DATA SOURCES: Studies were retrieved from a systematic search of published works indexed in CINAHL, MEDLINE (PubMed), Science Direct and the Cochrane Central Register of Controlled Trials (CENTRAL). METHODS: A systematic review of effectiveness was conducted using the Cochrane Effective Practice and Organisation of Care guidelines and a narrative synthesis approach for data handling and presentation. The review period was 1992 to 31 August 2008. RESULTS: Nursing assessment and referral interventions have demonstrated effectiveness in reducing service use and improving physical function, but have failed to demonstrate statistically significant effects on predicted patient and/or health systems outcomes. CONCLUSION: The evidence of the effectiveness of gerontologically informed nursing assessment and referral interventions in EDs must be accepted with caution, as not all studies demonstrated effectiveness in predicted patient and/or health systems outcomes, and the testing of complex social interventions in randomized clinical trials is inherently problematic. Further evidence of the effectiveness of nursing interventions is required, and such evidence might be usefully demonstrated using pragmatic, as opposed to explanatory, trials.